ANALISIS PENGARUH VARIASI PH LARUTAN ACID ZINC PADA SEL VOLTA DUA KOMPARTEMEN DENGAN ELEKTRODE Cu(Ag)-Zn - Gurum Ahmad Pauzi; Nilla Anggi Pratiwi; Arif Surtono; Sri Wahyu Suciyati (Journal of Energy, Material, and Instrumentation Technology, 2022)
The research was conducted to analyze the effect of variations in pH of acid zinc solution in two compartment voltaic cells with Cu(Ag)-Zn electrodes on the value of electrical characteristics and the resulting corrosion rate. The Cu(Ag)-Zn pair is used to generate voltage and current in the cell with seawater electrolyte and zinc acid solution. The two compartments are lined with salt bridge made from mixture of Al2O3 (aluminum oxide), NaCl (seawater) 1 mole concentration dissolved in “tiga roda” white cement. The voltaic cell consisted of 5 cells arranged in series circuit, for each cell at the cathode (Cu(Ag)) containing ± 250 ml seawater and at the anode (Zn) containing ± 200 ml cid zinc solution which was varied with a pH of 4.5 and 6. The voltaic cell was measured with multitester every 1 hour for 3 days. Based on the research that has been done, it can be concluded that by using an acid zinc electrolyte solution which has a lower pH value, it will increase the value of the electrical characteristics and increase the corrosion rate produced by voltaic cell.